In the eye of the beholder: subjective inequality measures and the demand for redistribution - Andreas Kuhn (Institute for the Study of Labor (IZA), 2009)
This paper presents a simple conceptual framework intended for describing individuals' subjective evaluations of occupational wage inequality and their demand for redistribution. Most importantly, the framework explicitly allows for the distinction between individuals' perceptions and their normative beliefs. I illustrate the framework using Swiss survey data from the International Social Survey Program. While most individuals accept quite large wage differentials across occupations, they also prefer a lower level of overall wage inequality than what they perceive to exist. Consistent with previous evidence, the empirical analysis also shows that financial self-interest, social norms about distributive justice and perceptions of how wages are determined in reality all simultaneously influence the demand for redistribution. Finally, I show that subjective inequality measures and the demand for redistribution are substantially significant predictors of both individuals' support for government intervention and their party identification. This result provides indirect evidence on the presumed link between perceptions and beliefs on the one hand and political outcomes on the other hand.
urn:nbn:de:101:1-20091105781
Keywords: D3; D63; H1; 330; Subjective inequality measures; demand for redistribution; distributive justice; party identification; support for the welfare state; Lohnstruktur; Meinung; Verteilungsgerechtigkeit; Einkommensumverteilung; Verteilungspolitik; Politische Partei; Präferenztheorie; Schweiz